Real-Time Flash Glucose Monitoring Had Better Effects on Daily Glycemic Control Compared With Retrospective Flash Glucose Monitoring in Patients With Type 2 Diabetes on Premix Insulin Therapy - Yan, Reng-na; Cai, Ting-ting; Jiang, Lan-lan; Jing, Ting; Cai, Ling; Xie, Xiao-jing; Su, Xiao-fei; Xu, Lan; He, Ke; Cheng, Liang; Cheng, Cheng; Liu, Bing-li; et al. (Frontiers in Endocrinology, 2022)
Background and Aims: To compare the effects of real-time and retrospective flash glucose monitoring (FGM) on glycemic variability and lifestyle in patients with type 2 diabetes on premix insulin therapy. Methods and Results: A total of 172 patients using premix insulin, with HbA1c ≥ 7.0% (56mmol/mol), or the time below the target (TBR) ≥ 4%, or the coefficient of variation (CV) ≥36% during the screening period, were randomly assigned to retrospective FGM (n=89) or real-time FGM group (n=83). Another two retrospective or real-time 14-day FGMs were performed respectively, one month apart. Both groups received educations and medication adjustment after each FGM. Time in range (3.9 10.0 mmol/L, TIR) increased significantly after 3 months in the real-time FGM group (6.5 %) compared with the retrospective FGM group (-1.1%) (P =0.014). HbA1c decreased in both groups (both P <0.01). Real-time FGMs decreased TBR and CV, and increased daily exercise time (P all <0.01), while the mean calories intake per meal increased during the third FGM compared with baseline only in the retrospective group (P =0.023). Conclusions: Real-time FGM with visible blood glucose improves glycemic variability better than retrospective FGM via improvement of diabetes self-care behaviors in patients with type 2 diabetes on premix insulin therapy.